(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
Due to the importance of generating electricity from wind turbines, single rotor wind turbine and dual rotor wind turbine, there was a need to design and manufacture the turbine system operating in both types mentioned above and have advantages to increase the generation of electric power. The aim of this work was to generate electrical power at a wind speed of up to 1m/s and more to achieve this wind speed and direction of the wind were adopted from tables of the Zerbatiya Station of the Wasit Governorate. Controlling the work is by Adaptive Controller technology, as well as the programming language which used is Visual Studio 2015.The simulation was used to generate rotational speed for front and rear blades from 1m/s to 13m/s. Movable wings were placed in the manufactured system which rotate at angle of 0o-14o for the purpose of studying the effect of the tilt angle of the blades on power generation. The following were added to the system: mechanism to separate the work of the front and rear rotors and a device to reverse the rotation of these rotors. The Genetic Algorithm (GA) was used within the program for the purpose of obtaining the best of generated power. All the above were for the purpose of determining the best position for blades at different speeds to generate electricity by using Permanent Magnet Synchronous Generator (400W). The maximum generated power in dual wind turbine (DWT) when rotate the front and rear blades in same direction was obtained at speed (151rpm) in used tilt angle ofmovable wing is about (12ο) and power (124.223W)also the separation mechanism and rotation reversing device proved efficiency.